Solid state science and technology IV : selected, peer reviewed papers from the 4th International Conference on Solid State Science and Technology, (ICSSST 2012), December 18-20, 2012, Melaka, Malaysia - International Conference on Solid State Science and Technology (4th : 2012 : Melaka, Malaysia); Huang, Nay Ming, editor; Saadah Abd Rahman, editor; Woon, Kai Lin, editor (Switzerland : Trans Tech Publication, 2014)
Includes bibliographical references and index.